Impact of Covid - 19 infection and its severity during pregnancy in 2021 - a retrospective observational study - Payal P Panchal; Bina M Raval; Shashwat K Jani; Purvi M Parikh; Sushma R Shah; Anushka S Mehta; Svija R Ghanchi (Barpeta Obstetrics and Gynaecological Society, 2023)
Objectives: 1. Categorisation of disease severity in pregnant covid patients, 2. Evaluation of disease progression and severity in different trimesters of pregnancy and 3. Correlation of severity with laboratory parameters, treatment protocol and pregnancy outcome at our tertiary care centre. Methods: This retrospective observational study was carried out at a tertiary care hospital from 1st January 2021 to 30th June 2021. 122 covid 19 positive pregnant females were analysed for categorisation and comparison of severity, management protocol and disease outcome. Results: 46 out of 122 antenatal patients (37.70%) needed oxygen support and 22% were severely affected. Most commonly reported clinical symptoms were fever (63.3%), cough (71.4%) and dyspnoea (34.4%). CRP was found to be significantly affected with disease severity (p<0.00001). Patients in second trimester were observed to require remdesevir more frequently than others because they were observed to be more severely affected. Patients who were admitted after one week of symptom onset were more severely affected than the patients who were admitted within 5days of symptom onset. Majority [47 (74.6%) of the 63 patients] who terminated pregnancy underwent cesarean section. Of the 14 patients that died, 11 patients had symptoms for more than 10 days. Conclusion: Pregnancy had a severe impact on the course of covid-19 infection. Covid infection led to more adverse pregnancy outcomes than those who were not affected by covid-19 in view of maternal respiratory distress that led to increase maternal mortality.